Function and therapeutic prospects of next-generation probiotic Akkermansia muciniphila in infectious diseases - Li, Lifeng; Li, Mingchao; Chen, Yihua; Yu, Zengyuan; Cheng, Ping; Yu, Zhidan; Cheng, Weyland; Zhang, Wancun; Wang, Zhaobao; Gao, Xueyan; Sun, Huiqing; Wang, Xiaolei (Frontiers in Microbiology, 2024)
Akkermansia muciniphila is a gram-negative bacterium that colonizes the human gut, making up 3–5% of the human microbiome. A. muciniphila is a promising next-generation probiotic with clinical application prospects. Emerging studies have reported various beneficial effects of A. muciniphila including anti-cancer, delaying aging, reducing inflammation, improving immune function, regulating nervous system function, whereas knowledge on its roles and mechanism in infectious disease is currently unclear. In this review, we summarized the basic characteristics, genome and phenotype diversity, the influence of A. muciniphila and its derived components on infectious diseases, such as sepsis, virus infection, enteric infection, periodontitis and foodborne pathogen induced infections. We also provided updates on mechanisms how A. muciniphila protects intestinal barrier integrity and modulate host immune response. In summary, we believe that A. muciniphila is a promising therapeutic probiotic that may be applied for the treatment of a variety of infectious diseases.